1998
DOI: 10.1074/jbc.273.22.13776
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the GAL4 DNA-binding Domain Can Affect Transcriptional Activation Independent of DNA Binding

Abstract: The GAL4 protein belongs to a large class of fungal transcriptional activator proteins encoding within their DNA-binding domains (DBD) six cysteines that coordinate two atoms of zinc (the Zn 2 Cys 6 domain). In an effort to characterize the interactions between the Zn 2 Cys 6 class transcriptional activator proteins and their DNAbinding sites, we have replaced in the full-length GAL4 protein small regions of the Zn 2 Cys 6 domain with the analogous regions of another Zn 2 Cys 6 protein called PPR1 an activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
(39 reference statements)
4
21
0
Order By: Relevance
“…Cooperativity here refers to the facilitation of the binding of transcription factors by the previous binding of transcription factors (Ptashne and Gann 2002). Experimental work has shown that the number of cis-regulatory elements, nucleotide variation in these elements, amino acid differences in DNAbinding domains of transcription factors, variation in cooperativity among transcription factors, or variation in the recruitment of the general transcription machinery can independently, but not necessarily additively, lead to changes in expression level (Hill et al 1986;Gill et al 1990;Beckett et al 1993;Corton et al 1998;Oda et al 1998;Burz and Hanes 2001;Inga et al 2002;Monti et al 2002). Models of gene regulation that have included these variables (Gibson 1996;Veitia 2003) have made the clear prediction that changes in many parameters can lead to similar gene expression levels and therefore that similar levels of gene expression between species can conceal genetic divergence in the regulatory elements.…”
Section: Appendix-model Of Gene Expression Regulationmentioning
confidence: 99%
“…Cooperativity here refers to the facilitation of the binding of transcription factors by the previous binding of transcription factors (Ptashne and Gann 2002). Experimental work has shown that the number of cis-regulatory elements, nucleotide variation in these elements, amino acid differences in DNAbinding domains of transcription factors, variation in cooperativity among transcription factors, or variation in the recruitment of the general transcription machinery can independently, but not necessarily additively, lead to changes in expression level (Hill et al 1986;Gill et al 1990;Beckett et al 1993;Corton et al 1998;Oda et al 1998;Burz and Hanes 2001;Inga et al 2002;Monti et al 2002). Models of gene regulation that have included these variables (Gibson 1996;Veitia 2003) have made the clear prediction that changes in many parameters can lead to similar gene expression levels and therefore that similar levels of gene expression between species can conceal genetic divergence in the regulatory elements.…”
Section: Appendix-model Of Gene Expression Regulationmentioning
confidence: 99%
“…The Gal4 activator functions to stimulate transcription in all eukaryotes tested, from yeast to humans, and activates transcription when fused to a heterologous DNA binding domain (5,41). The Gal4 DNA binding domain has no activation activity when separated from the activating regions, although mutations within this domain have been reported to reduce activation in vivo (12).…”
mentioning
confidence: 99%
“…We found recently that the proteasomal ATPases, including Sug1/Rpt6 and Sug2/Rpt4, potently destabilize Gal4-and Gal4-VP16-promoter complexes in an ATP-dependent fashion (23). As would be anticipated, this activity strongly represses the function of the activator (23,56). However, we found that monoubiquitylation of the Gal4 DNA-binding domain blocks this inhibitory effect (23).…”
Section: Discussionmentioning
confidence: 68%